A benzimidazole‐linked porphyrin covalent organic polymers as efficient heterogeneous catalyst/photocatalyst. (22nd July 2022) - Wei, Jiaojiao; Wang, Dan; Li, Jun; Zhang, Jiale; Wang, Ning; Li, Jun
Abstract : Porphyrins are selected as building units to synthesize porphyrin‐based covalent organic polymers (COPs), which can combine the excellent properties of covalent organic polymers with the fantastic catalytic effect of porphyrin to obtain a heterogeneous catalyst with excellent catalytic activity. In this work, the novel benzimidazole‐linked porphyrin COPs MPp‐BTA (M = 2H, Zn, Co) were synthesized using a new porphyrin with aldehyde group peripherally MPp (M = 2H, Zn, Co) and 1, 2, 4, 5‐tetraminobenzene tetrahydrochloride (BTA) as monomers. The synthesized MPp‐BTA were carefully characterized by FT‐IR, UV–vis, SEM, TEM, TG, and PXRD. As heterogeneous catalyst, MPp‐BTA (M = Zn, Co) shows the high catalytic activity and stability for cycloaddition of CO2 with phenyl glycidyl ether (PGE) under mild conditions (80°C, 0.1 MPa CO2 ), and the yield of cyclocarbonate can reach 95% and 92% respectively. In addition, the recycling stability of ZnPp‐BTA was investigated, and the yield of cyclocarbonate was still remained at 86% after five cycles. Furthermore, MPp‐BTA (M = 2H, Zn, Co) can be used directly as heterogeneous photocatalysts for selective oxidation of thioanisole to methyl phenyl sulfoxide. To our delight, H2 Pp‐BTA shows satisfactory photocatalytic performance, and the yield of methyl phenyl sulfoxide can reach 93% in 4 h. Abstract : A novel benzimidazole‐linked porphyrin COPs MPp‐BTA (M = 2H, Zn, Co) was synthesized using a new porphyrin with aldehyde group peripherally MPp (M = 2H, Zn, Co) and 1, 2, 4, 5‐tetraminobenzene tetrahydrochloride (BTA) as monomers through Schiff base reaction. As heterogeneous catalysts, MPp‐BTA shows the highly catalytic activities and stabilities for cycloaddition reaction of CO2 with phenyl glycidyl ether (PGE) under mild conditions (80°C, 0.1 MPa CO2). Furthermore, MPp‐BTA can be used as heterogeneous photocatalysts for selective oxidation of thioanisole to methyl phenyl sulfoxide.